Olanzapine increases hepatic glucose production through the activation of hypothalamic adenosine 5′‐monophosphate‐activated protein kinase. Issue 12 (11th July 2013) - Ikegami, M.; Ikeda, H.; Ohashi, T.; Ohsawa, M.; Ishikawa, Y.; Kai, M.; Kamei, A.; Kamei, J.
Abstract : Aims: To investigate the mechanism of the metabolic disturbance induced by the atypical antipsychotic olanzapine, we examined whether adenosine 5′‐monophosphate‐activated protein kinase (AMPK) in the hypothalamus and hepatic glucose production are involved in the effect of olanzapine. Methods: Male 6‐week‐old ICR mice were used. Blood glucose levels were determined by the glucose oxidase method. The mRNA levels of gluconeogenic or glycolytic enzymes were measured by reverse transcription polymerase chain reaction (RT‐PCR). AMPK expression was measured by Western blotting. Results: Systemic injection of olanzapine increased blood glucose levels in both unfasted and fasted mice. However, the increase in fasted mice was less than that in unfasted mice. Central administration of olanzapine also increased the blood glucose levels in unfasted mice, but not in fasted mice. In a pyruvate tolerance test, olanzapine significantly increased blood glucose levels. In addition, olanzapine increased the mRNA levels of glucose‐6‐phosphatase (G6Pase), a gluconeogenic enzyme, in the liver. Furthermore, olanzapine increased phosphorylated AMPK in the hypothalamus of unfasted mice, and olanzapine‐induced hyperglycaemia was inhibited by the AMPK inhibitor compound C. Central administration of the AMPK activator AICAR significantly increased G6Pase mRNA levels in the liver and blood glucose levels. Moreover, both olanzapine‐ and AICAR‐induced hyperglycaemia were attenuated by the β ‐adrenergic receptor antagonist propranolol, suggesting that olanzapine and AICAR induce hepatic glucose production through the sympathetic nervous system. Conclusions: Our results indicate that olanzapine activates AMPK in the hypothalamus, which increases hepatic glucose production via the sympathetic nervous system.